In vitro binding capacity of free bilirubin by aqueous extract of Marrubium vulgare L. - Stayeb, Sara; Mahmoud Adel Chabane; Boukada, Fadhéla; Belgharbi, Asmaa; Boualem, Zineb; Bouchekara, Soumaya; Boukraa, Djamila (Acta Scientiarum. Biological Sciences, 2025)
Marrubium vulgare L. (MVL.) has been traditionally used to treat kernicterus. However, the anti-jaundice effects and mechanisms of MVS. on free bilirubin remain poorly understood. The present study assesses the anti-jaundice effect of the aqueous extract of MVL, by measuring the percentage of adsorption (binding) of this extract on plasmatic free bilirubin obtained from kernicterus newborns (n = 40). The plant’s aerian party and leaf pouder histological and phytochemical properties of MVL were examined. Our results show that dry aqueous extract of MVL contains total phenols (51.5 ± 0.40 mg EAG g-1), condensed tannins (14.7 ± 0.49 mg ECAT g-1) and flavonoids (25.33 ± 0.41 mg ECAT g-1). Histological examination showed that both the surfaces of leave and stems are covered by a protective hair; glandular and non-glandular trichomes which produced various secondary metabolites. Free bilirubin was significantly bound by the aqueous extract of MVL at different concentrations (250-1250 µg ml-1) to the extent of (33.6 - 54.61%). In the light of these preliminary findings and future experimental studies, it indicates that this plant may be used as a source of therapeutic agent for kernicterus and can be an alternative treatment to the currently available treatments such as phototherapy and exsanguino-transfusion, which have serious short and long term complications.